Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1186/1471-2458-7-217
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviors and risk factors in those who use complementary and alternative medicine

Abstract: BackgroundSurveys have generally found that individuals more likely to use complementary and alternative medicine are female, live in the western United States, are likely to have a health complaint, and have a higher socioeconomic status than do nonusers. What is not known is the extent to which those who use complementary and alternative medicine also engage in positive health behaviors, such as smoking cessation or increased physical activity and/or exhibit fewer health risk factors such as obesity. This ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
100
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 25 publications
11
100
1
3
Order By: Relevance
“…Perceived risk and engaging in breast cancer screening behaviors dropped out, likely owing to correlation with variables retained in the model. Our results are consistent with previous population-based survey findings in healthy samples where CAM use correlated with general health behaviors (25) and education (9,10).…”
Section: Discussionsupporting
confidence: 92%
“…Perceived risk and engaging in breast cancer screening behaviors dropped out, likely owing to correlation with variables retained in the model. Our results are consistent with previous population-based survey findings in healthy samples where CAM use correlated with general health behaviors (25) and education (9,10).…”
Section: Discussionsupporting
confidence: 92%
“…While Asians and whites typically have the highest percentages of CAM use, studies have shown variation between the two groups. Some have shown Asians as more likely users of CAM than whites, 17,18 as equally likely, 19 or as less likely. 3 In part, these differences may be attributed to the heterogeneity within Asian subgroups with regard to culture, lifestyle, and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Interesują się profilaktyką chorób oraz zdrowym stylem życia, co uwidacznia się poprzez częściej podejmowaną aktywność fizyczną, mniejsze spożycie alkoholu, nie palenie tytoniu czy zdrową dietę [11]. Stosowanie niekonwencjonalnych metod terapii utwierdza ich w przekonaniu, że zdrowie jest w ich własnych rękach, a jego przywrócenie lub utrzymanie leży w zakresie ich działań [12].…”
Section: Wstępunclassified
“…[3] wynika, że światopogląd albo też filozofia życiowa kobiet jest zgodna z tą, którą zawierają w sobie niekonwencjonalne metody terapii (holizm, aktywna rola w umacnianiu zdrowia, podmiotowość). Niekonwencjonalne metody terapii mogą w większym stopniu zaspokajać potrzeby kobiet i pomagać radzić sobie z sytuacją choroby [12].…”
Section: Dyskusjaunclassified
See 1 more Smart Citation